Advances in Integrated Design and Manufacturing in Mechanical Engineering II - Tichkiewitch, Serge; Tollenaere, M.; Ray, Pascal (Springer Netherlands : Imprint: Springer, 2007)
The 33 papers presented in this book were selected from amongst the 97 papers presented during the sixth edition of the International Conference on Integrated Design and Manufacturing in Mechanical Engineering during 28 sessions. Two keynote papers, one presented by Professor Stephen Lu, from the IMPACT Research Laboratory, University of Southern California, USA, on "Supporting participative joint decisions in integrated design and manufacturing teams", and one written by Professor Stefan Rudolph from Stuttgart University about "Know-How Reuse in the conceptual design phase of complex engineering products or: 'Are you still constructing manually or do you generate already automatically", introduce the subject of the Conference and are followed by the different themes highlighted during the conference: The design/manufacturing interface; Integrated design of manufacturing processes; Life cycle design and manufacturing approaches; Agility in design and manufacture; Knowledge in engineering; and Management in production systems.